2023
DOI: 10.3389/fpsyg.2022.1019024
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on impulse consumption intention of livestreaming e-commerce: The mediating effect of flow experience and the moderating effect of time pressure

Abstract: Based on the Stimulus-Organism-Response (S-O-R) model, this paper studies the impulsive consumption mechanism of consumers participating in livestreaming e-commerce from the perspectives of information source characteristics and social presence and examines the mediating effect of flow experience and the moderating effect of time pressure. Based on the consumption data of 268 live shoppers, multiple regression analysis and Bootstrap method were used to test the research hypothesis. The empirical results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Some researchers have studied the mechanism underlying the purchase intention of consumers from many perspectives including information technology (IT) affordance (Sun et al, 2019), online celebrity-product, product-livestreaming content matching (Park and Lin, 2020), swift guanxi (Zhang et al, 2020), reducing uncertainty (Lu and Chen, 2021), eye-tracking experiments (Fei et al, 2021), emotional contagion (Meng et al, 2021), emotional intermediary (Zhou and Tong, 2022) and mental imagery quality and customer trust (Wang et al, 2022). Other researchers have studied impulse buying in live e-commerce from perspectives including popularity cues (Lou et al, 2022), human-computer interaction (Yang et al, 2022), flow experience and time pressure (Dong et al, 2023), information transparency (Xu et al, 2022), livestreaming interactions (Liu et al, 2022) and extending the elaboration likelihood model with herd behavior (Yang and Lee, 2023).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have studied the mechanism underlying the purchase intention of consumers from many perspectives including information technology (IT) affordance (Sun et al, 2019), online celebrity-product, product-livestreaming content matching (Park and Lin, 2020), swift guanxi (Zhang et al, 2020), reducing uncertainty (Lu and Chen, 2021), eye-tracking experiments (Fei et al, 2021), emotional contagion (Meng et al, 2021), emotional intermediary (Zhou and Tong, 2022) and mental imagery quality and customer trust (Wang et al, 2022). Other researchers have studied impulse buying in live e-commerce from perspectives including popularity cues (Lou et al, 2022), human-computer interaction (Yang et al, 2022), flow experience and time pressure (Dong et al, 2023), information transparency (Xu et al, 2022), livestreaming interactions (Liu et al, 2022) and extending the elaboration likelihood model with herd behavior (Yang and Lee, 2023).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…, 2022), human-computer interaction (Yang et al. , 2022), flow experience and time pressure (Dong et al. , 2023), information transparency (Xu et al.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Xu et al (2021) found that the sense of presence induced by individuals watching online live-streamed shopping positively influences their purchase intention. Additionally, Dong et al (2023) highlighted the significance of presence in live e-commerce, where it serves as a crucial incentive for consumers to experience flow and develop impulse consumption intentions. Building on this literature, our study posits that a higher sense of presence experienced by individuals when browsing destination environmental threat information through digital media facilitates a deeper understanding of the destination’s ecological environment, thereby stimulating TPEBI.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…However, social influence is often interpreted as the presence and the number of other viewers ( Leeraphong and Sukrat, 2018 ; Ko and Chen, 2020 ; Zhang et al, 2022b ), the features of streamers ( Wang et al, 2018 ; Hou et al, 2019 ; Ko and Chen, 2020 ; Park and Lin, 2020 ; Xu et al, 2020a ; Zheng et al, 2023 ), and the action and enthusiasm of sellers ( Leeraphong and Sukrat, 2018 ). Besides, as for the internal mechanism of environmental cues inducing behavior, previous research has emphasized the mediating role of relationship status, flow experience ( Dong et al, 2023 ), personal characteristics ( Gao et al, 2022 ), and community-triggered emotions ( Lim et al, 2020 ; Li et al, 2021 ), few studies have focused on personal emotional changes ( Xu et al, 2023 ) and emotional subdivided dimensions. Moreover, while the uncertainty concern surrounding experience products is a critical barrier to online consumption, few studies have offered concrete suggestions on how to eliminate it.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%